USM TO ASSIST INDUSTRY THROUGH COLLABORATIONS IN LONG-TERM RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM would like to extend its gratitude for all the comments and concerns voiced in relation to the agreement with a certain company signed recently.